A Computational Study of an Optimized MOS-Like Graphene Nano Ribbon Field Effect Transistor (GNRFET). (17th February 2018) - Khorshidsavar, Amin; Ghoreishi, Seyed Saleh; Yousefi, Reza
Abstract : The present paper introduces a metal-oxide-semiconductor graphene nanoribbon field-effect transistor (MOS-GNRFET), in which heterogeneous gates with different work functions have been used. In this structure, length of each gate was selected equal to 15 nm; moreover, work function of the gate close to the source and drain was selected equal to and 0.4 eV less than the graphene nanoribbon's work function, respectively. The simulation was performed using the non-equilibrium Green's function (NEGF) in the mode space approach. According to the simulation results, the proposed structure exhibited better ambipolar behavior and had less off-current compared with the conventional structure with the same dimensions. In addition, the hot electron effect is reduced in the proposed structure.